Development of football sports agility model in special preparation stage - Prasetyo, Afif Bayu; Doewes, Muchsin; Purnama, Sapta Kunta (Journal of Education, Health and Sport, 2019)
The purpose of this study is the need for appropriate soccer sports agility training models at the special preparation stage. This study aims to develop a soccer training model at a special preparation stage to improve agility. The research method used in this research is the development research method proposed by Brog and Gall. The researcher adapted the research procedure into 3 stages, namely: the needs analysis stage, the product development stage, and the product effectiveness test stage. At the needs analysis stage, the interview method with soccer coaches was stated which stated that there was a need to develop a new training model to improve agility. The second stage is the product development stage with expert judgment with a percentage of 82%. Furthermore, product testing, the results of small group trials with a percentage value of 80% and in large group trials with a percentage value of 85.78%. Next in the third stage is the product effectiveness test by comparing experimental groups using an exercise model developed with a control group that uses conventional training. The design of the experimental design uses the Two Group pre test post test desgin design. Different values of T-scores for the agility test of the experimental group 85.22 and the control group 40.33. The development of a soccer training model proved to be significant in increasing agility at the special preparation stage.